Bridging the Gap: Understanding Embryonic Intervertebral Disc Development - Sivakamasundari (2012)
The intervertebral disc (IVD) is a multi-component structure consisting of a heterogeneous population of cells that form the central nucleus pulposus, encased by the fibrous annulus fibrosus and the cartilage end-plate. The essential function of the IVD is to withstand biomechanical forces, confer tensile strength and flexibility in motion to the spine. Disc degenerative disease (DD) is a prevalent ailment that affects the general population, often manifesting either in the form of lower back pain or as deformities of the spine such as degenerative lumbar scoliosis or in severe cases as disc herniation. With the aid of mutant mouse models generated through traditional knock-out strategies and spontaneous mutants, scientists have been able to elucidate some of the fundamental mechanisms of embryonic IVD development. Mutual interaction between the notochord and vertebral bodies are instrumental in the proper formation of the IVD. In this review, the known and proposed molecular mechanisms underlying these processes and the areas that require further investigation are discussed. Sufficient knowledge on the molecular mechanisms of IVD formation and the etiology of IVD degeneration is currently lacking and this has greatly hampered efforts to design appropriate and effective therapies for DD. With the dawn of the next-generation sequencing and better tools to engineer the genome, elucidation of the mechanism of IVD formation and the molecular basis of the pathology of DD ought to be an appealing avenue for researchers to pursue.